Social cognitive elements of mental illness stigma among healthcare professionals currently working in general hospitals: A cross‐sectional study from Jordan - Heyam F. Dalky; Malek Alnajar; Ala'a F. Dalky; Naser Mahmoud; Mohammad Al‐Ma'ani; Sultan Mosleh; Ayman M. Hamdan‐Mansour (Nursing Open, 2023)
Abstract Aim To assess the social cognitive elements of the stigma of mental illness (knowledge, attitudes and behaviours) among healthcare professionals (HCPs) in Jordan. Design A cross‐sectional descriptive design. Methods A total of 206 HCPs were conveniently recruited from general hospitals in Jordan. The mental attitude, knowledge and intended behaviours scales were used to measure stigma elements. Results Participants reported a moderate level of knowledge, a moderate negative attitude and a moderate or not greater interest to deal with people with mental health illnesses. The bivariate correlation revealed a negative significant correlation between HCPs' knowledge and attitude, indicating that HCPs with more knowledge significantly have more positive attitude (lower average score) towards those suffering from the illness. A more significant correlation was found between HCPs' knowledge and behaviour. The HCPs who had more knowledge were holding more interest and willingness towards dealing with persons with mental illness. Patient or Public Contribution Negative attitudes among HCPs demand awareness programmes pertaining to the stigma of mental illness to afford higher standards of practice for patients with mental problems.